Nice teams finish last : the secret to unleashing your team's maximum potential - Miller, Brian Cole, 1956- (American Management Association, 2010)
Don't rock the boat. Don't make waves. Don't offend anyone. There's a palpable feeling that clouds many team meetings and keeps them from being productive: over-politeness. And while the conflict that naturally exists in most organizations hasn't gone away, it manifests itself in passive-aggression, mediocrity, and a molasses-like inability to get anything done. Nice Teams Finish Last provides the antidote to this all-too-common tendency, giving managers, team leaders and members, and facilitators the practical support they need to battle "the nice trap" and start getting results! The book hel